2008
DOI: 10.1186/1471-2180-8-93
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction is superior to serology for the diagnosis of acute Mycoplasma pneumoniae infection and reveals a high rate of persistent infection

Abstract: BackgroundDiagnosis of Mycoplasma pneumoniae (MP) infection is traditionally based on serology, which may require more than two weeks for diagnostic antibodies to develop. PCR-based methods offer earlier diagnosis. During a community outbreak of MP infection, we compared semi-nested and real-time PCR of oropharyngeal swabs with serology for diagnosis of MP infection at different time points after disease onset. PCR-positive individuals were followed longitudinally to assess the persistence of MP DNA in throat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
120
2
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 30 publications
11
120
2
11
Order By: Relevance
“…La técnica empleada en nuestro laboratorio (IgM Elisa) tiene una sensibilidad y especificidad de 89,1 y 92,2% respectivamente. Nilsson comparó la sensibilidad de la PCR de secreciones respiratorias versus la detección serológica (IgG e IgM) en pacientes con infección respiratoria por Mycoplasma, destacando que la sensibilidad durante la primera semana del inicio de síntomas fue de 100% para la PCR y 23% para la serología 22 . La presencia de falsos positivos para IgM se puede ver en cuadros producidos por virus de Ebstein Barr, Citomegalovirus y Coronavirus.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La técnica empleada en nuestro laboratorio (IgM Elisa) tiene una sensibilidad y especificidad de 89,1 y 92,2% respectivamente. Nilsson comparó la sensibilidad de la PCR de secreciones respiratorias versus la detección serológica (IgG e IgM) en pacientes con infección respiratoria por Mycoplasma, destacando que la sensibilidad durante la primera semana del inicio de síntomas fue de 100% para la PCR y 23% para la serología 22 . La presencia de falsos positivos para IgM se puede ver en cuadros producidos por virus de Ebstein Barr, Citomegalovirus y Coronavirus.…”
Section: Discussionunclassified
“…La presencia de falsos positivos para IgM se puede ver en cuadros producidos por virus de Ebstein Barr, Citomegalovirus y Coronavirus. También se pueden ver valores intermedios de IgG e IgM en casos de Sarampión, Virus respiratorio sincicial, Virus Varicela zoster y Chlamidea pneumoniae 22 . En casos dudosos se recomienda la determinación de crioaglutininas.…”
Section: Discussionunclassified
“…It has been suggested that cross-reactivity with antigen preparations used in some of the commercial enzyme immunoassays (EIAs) result in over-diagnosis of M. pneumoniae infections [21]. Therefore, even if serology is a useful epidemiologic tool in areas where the infection rate of M. pneumoniae is high, it is less suited for assessment of individual patients in clinical laboratories [11].…”
Section: Discussionmentioning
confidence: 99%
“…Serological methods are currently the most common tool used in the clinical laboratory. However, these methods have practical limitations because of the availability of paired serum samples from both acute and convalescent phases, and provide results of questionable specificity and sensitivity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the sensitivity will increased to 100% (Souliou et al, 2007). The slow growth of M. pneumoniae coupled with lack of suitable commercially available culture media will limits the usefulness of cultural diagnosis and results in reliance on serology and the one of the newer techniques like PCR (Cassel et al, 1996), In the latter method, a nasal or throat swab specimens were analysed for the presence of M. pneumoniae and found it is an easy, reliable and quick diagnostic test in infants and children (Nilsson et al, 2008;Sorensen et al, 2013). We therefore conclude that IgM IFA assay showed relatively lower positivity than ELISA assay in the early acute phase and the use of the commercial ELISA assay in the country as a more reliable laboratory for the accurate and cost-efficient tool for diagnosis of specific IgM antibodies for Mycoplasma pneumoniae respiratory tract infections in children.…”
Section: Discussionmentioning
confidence: 99%